THEORETICAL AND PRACTICAL PROBLEMS OF MODERN PSYCHOLOGY - Семиченко, В. А. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
The article deals with the basic theoretical and methodological problems of modern psychology as a specific branch of science, methodological principles and key theoretical problems. Proved that psychology is most acutely feel the need to revise its foundations, because its theme is closely connected with all the methodological, methodical and organizational aspects of the learning process